Prokrastinasi: Problem Manajemen Waktu Mahasiswa? - Siti Mulyanah (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this research is to find out what factors influence academic procrastination in students and to create a measuring tool for academic procrastination. In this study report, a qualitative descriptive method was used by taking notes because the data source was obtained by listening to the oral narrative from the On Marissa's Mind YouTube channel entitled